Poster Presentation: Undergraduate EFL Student’s Experience - Ratu Sarah Pujasari (Script Journal: Journal of Linguistics and English Teaching, 2019)
This article briefly reports student’s experience on the use of Poster Presentation in an Indonesian EFL classroom. Its focus is to share the activities, to recognize student’s perspectives framing it and identify the benefit of Poster Presentation. Participants included a class of thirty-five, 1st-year English Education department in one of universities in Tasikmalaya, west java Indonesia; 23 females and 12 males. The findings revealed that most of the students demonstrated positive vibe and were satisfied toward using Poster Presentation activities; enjoying group poster preparation, stimulating good personal presentation, fostering student’s activeness and creativity and they reported a desire to engage in similar practices in the future.